Prevalence and Risk Factors of Giardiasis in Children with Persistent Watery Diarrhea: A Cross-Sectional Study - Shafqat Ali; Arit Parkash; Fahad Ali Mangrio; Shabana Shaikh (Journal of the Dow University of Health Sciences)
Objective: This study aimed to examine the prevalence and risk factors of giardiasis in children with persistent watery diarrhea at a tertiary care hospital Karachi, Pakistan. Methods: This cross-sectional study was conducted at the National Institute of Child Health in Karachi, Sindh, Pakistan, between November 2023 to April 2024. Children aged ≤15 years, with persistent watery diarrhea lasting more than six days were included in the study. The study assessed two primary outcomes, prevalence of giardiasis with persistent watery diarrhea and associated risk factors. Giardia was diagnosed by examining stool samples using fluorescent antibody testing to detect cysts and trophozoites of Entamoeba histolytica and Giardia lamblia. Risk factors were assessed based on children's demographic information and clinical history. Results: Of total 133 children, the mean age was 6.76 ±4.28 years. Giardiasis was detected in 18 (13.5%) children. The risk of giardiasis was 5 times significantly higher in children whose mothers did not practice handwashing before feeding (aOR 5.04, 95% CI 1.10 to 23.02, p-value 0.037) and had piped drinking water sources (aOR 5.47, 95% CI 1.24 to 24.08, p-value 0.025). While, 92% siginificantly lower in children who had adequate domestic water storage (aOR 0.08, 95% CI 0.01 to 0.48, p-value 0.006) and 93% significantly lower in children had no recent traveling history (aOR 0.07, 95% CI 0.01 to 0.49, p-value 0.007). Conclusion: This study identified giardiasis as a health concern, with infection risk influenced by maternal handwashing, domestic water storage, piped drinking water, and recent travel history.